PENGARUH PELATIHAN PEER EDUCATOR TERHADAP PENGETAHUAN TERKAIT TRIAD KESEHATAN REPRODUKSI REMAJA PADA KADER KESEHATAN DI SMA 11 SAMARINDA - Muhammad Bachtiar Safrudin; Della Saputri; Kartika Setia Purdani (An Idea Health Journal, 2025)
Background: Adolescent reproductive health is a critical issue that significantly influences the quality of life and future development of young people. The high incidence of sexually transmitted infections (STIs) and unintended pregnancies among teenagers underscores the urgent need for effective educational interventions. Peer educator training is considered a promising approach to improve adolescents' understanding and management of their reproductive health. This study aims to assess the effectiveness of peer educator training in enhancing adolescents’ knowledge and skills related to reproductive health. It also seeks to compare outcomes between the experimental and control groups. A quasi-experimental design was employed, involving two groups: an experimental group that received peer educator training and a control group that did not receive any intervention. Statistical analysis was conducted using independent and paired t-tests to examine significant differences within and between the groups. he analysis revealed a statistically significant improvement in knowledge within the experimental group, with a p-value of 0.000 (p < 0.05), indicating a substantial difference before and after the training. Furthermore, the post-intervention comparison between the experimental and control groups also showed a significant difference in knowledge levels (p = 0.000), supporting the effectiveness of the training intervention conducted at SMA 11 Samarinda.Peer educator training is effective in increasing adolescents' knowledge regarding reproductive health. This intervention can serve as a valuable model for youth health education programs. Sustained efforts are recommended to broaden its implementation and maximize its impact on adolescent health outcomes